Holistic curriculum management based on local wisdom in elementary education: a case study of Bukit Batu Tourism Village - Siti Febrianti; Setya Raharja; Juwandi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This research is motivated by the low integration of local cultural values in the elementary school curriculum which causes less contextual learning. The purpose of this study is to analyze the pattern of curriculum management based on local wisdom in SD Negeri 11 Bukit Batu. The research method used is qualitative with phenomenological design through interviews, observations, and documentation studies. The results of the study showed that curriculum planning was carried out in a participatory manner, the organization was focused on the division of teacher roles and activity scheduling, implementation was realized through contextual learning, P5 projects, and zapin and kompang cultural arts activities, while the evaluation emphasized the relevance of materials, methods, student involvement, facilities, and learning outcomes achievements. The novelty of this research lies in the mapping of a holistic curriculum management pattern that balances academic competence with the preservation of local culture. The conclusion shows that this model is able to increase the relevance of learning while strengthening students' character.